Quantitative Affinity Chromatography. Determination of Binding Constants by Elution with Competitive Inhibitors - Dunn, Ben M. (1974)
The affinity chromatographic separation procedure was tested for its utility in quantitating the affinity of proteins to both insolubilized ligand and corresponding competing soluble ligand. An expression has been derived that (1) allows the determination of binding constants for the interaction of a soluble protein species with an affinity chromatography matrix involving active site binding, (2) yields binding constants for the interaction of the protein with soluble ligands that can compete with the insoluble matrix for binding to the active site of the protein, and (3) utilizes readily obtainable parameters from conventional chromatography. This expression has been applied to the quantitation of the binding of staphylococcal nuclease to thymidine-5′-phosphate-3′-amino-phenylphosphate-Sepharose in competition with thymidine-3′,5′-bisphosphate.